2009
DOI: 10.1186/1477-3155-7-7
|View full text |Cite
|
Sign up to set email alerts
|

Backstep scanning ion conductance microscopy as a tool for long term investigation of single living cells

Abstract: Scanning ion conductance microscopy (SICM) is a suitable tool for imaging surfaces of living cells in a contact-free manner. We have shown previously that SICM in backstep mode allows one to trace the outlines of entire cell somata and to detect changes in cellular shape and volume. Here we report that SICM can be employed to quantitatively observe cellular structures such as cell processes of living cells as well as cell somata of motile cells in the range of hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 23 publications
1
54
0
Order By: Relevance
“…In the direct current (DC) mode, DC ion current is recorded during scanning, while, in the alternating current (AC) mode, the amplitude of the AC ion current modulated by oscillating the pipette probe is detected by using a lock-in amplifier (Pastré et al, 2001). In the hopping or backstep mode, ion current is recorded while the pipette is moved vertically and repeatedly approaches and retracts from the sample surface (Novak et al, 2009;Happel and Dietzel, 2009). Thus, this mode is also referred to as approach-retract scanning (ARS) mode.…”
Section: Scanning Ion-conductance Microscopy (Sicm)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the direct current (DC) mode, DC ion current is recorded during scanning, while, in the alternating current (AC) mode, the amplitude of the AC ion current modulated by oscillating the pipette probe is detected by using a lock-in amplifier (Pastré et al, 2001). In the hopping or backstep mode, ion current is recorded while the pipette is moved vertically and repeatedly approaches and retracts from the sample surface (Novak et al, 2009;Happel and Dietzel, 2009). Thus, this mode is also referred to as approach-retract scanning (ARS) mode.…”
Section: Scanning Ion-conductance Microscopy (Sicm)mentioning
confidence: 99%
“…Since then, SICM has been used to image the surfaces of different cultured cells such as neurons and cardiomyocytes (Gorelik et al, 2006(Gorelik et al, , 2004Happel et al, 2003;Pastré et al, 2001;Korchev et al, 2000). Recent advances in SICM have also provided a hopping mode (also called a backstep mode or approachretract scanning mode), in which the pipette is moved vertically and repeatedly approaches and retracts from the sample surface (Novak et al, 2009;Happel and Dietzel, 2009). This mode was especially Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The Besenbacher group reported that imaging the same sample using SICM in ac mode at a modulation frequency of 1 kHz is five times slower than using conventional AFM in tapping mode at 34 kHz [2]. Another well-known SICM imaging mode is the hopping mode [4] and its variants [19]- [22]. By functioning as conducting an approach curve at every point, the hopping mode and its variants are able to image steep obstacles without collisions and are therefore suitable for imaging complex samples.…”
Section: In-phase Bias Modulation Mode Of Scanningmentioning
confidence: 99%
“…Those modes include the direct current (DC), 8,22 alternate current (AC), [23][24][25] and hopping modes. [26][27][28] DC mode was first utilized to demonstrate live cell imaging as it maintains a constant direct current on the sample surface during raster scanning. Since the direct current maintains the tip-sample distance while the scanning probe follows the lateral topography, it has an inherent limitation for scanning larger or coarse objects.…”
Section: Introductionmentioning
confidence: 99%
“…29 In order to circumvent the aforementioned challenges with SICM imaging, the hopping probe ion conductance microscope (HPICM) was introduced enabling the scanning probe to be retracted after each positional recording. [26][27][28] In this mode, the probe approaches the sample until reaching the given setpoint vertically and records the distance from the initial z-position, returns to the initial z-position, and then laterally moves to the next position. Possible interference of coarse or fluctuating morphology is minimized using this non-continuous scan approach.…”
Section: Introductionmentioning
confidence: 99%